2021
DOI: 10.1053/j.ajkd.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A Roadmap for Innovation to Advance Transplant Access and Outcomes: A Position Statement From the National Kidney Foundation

Abstract: Over the past 65 years, kidney transplantation has evolved into the optimal treatment for patients with kidney failure, dramatically reducing suffering through improved survival and quality of life. However, access to transplant is still limited by organ supply, opportunities for transplant are inequitably distributed, and lifelong transplant survival remains elusive. To address these persistent needs, the National Kidney Foundation convened an expert panel to define an agenda for future research. The key prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 84 publications
0
40
0
Order By: Relevance
“…Beginning in December of 2019, the National Kidney Foundation (NKF) brought together kidney transplant scientists, nephrologists, and surgeons from across the country to discuss research priorities aimed at increasing the number of adults and children with kidney failure who are successful transplant recipients. 4 In 2021, Research Roundtables (preclinical and clinical research) were conducted to identify priorities for preclinical and clinical kidney-related research. The 2021 Roundtables comprised nephrology leaders from prominent academic institutions in the United States, the pharmaceutical industry, and key bodies with expertise in the multiple areas of preclinical and clinical research, including pediatric and adult nephrology, genetics, epidemiology, drug development, public health, and health equity.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning in December of 2019, the National Kidney Foundation (NKF) brought together kidney transplant scientists, nephrologists, and surgeons from across the country to discuss research priorities aimed at increasing the number of adults and children with kidney failure who are successful transplant recipients. 4 In 2021, Research Roundtables (preclinical and clinical research) were conducted to identify priorities for preclinical and clinical kidney-related research. The 2021 Roundtables comprised nephrology leaders from prominent academic institutions in the United States, the pharmaceutical industry, and key bodies with expertise in the multiple areas of preclinical and clinical research, including pediatric and adult nephrology, genetics, epidemiology, drug development, public health, and health equity.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, the National Kidney Foundation released a roadmap identifying 7 major priorities for research innovation: expanding living donation, improving waitlist management, increasing patient and clinician acceptance of organs, decreasing non-utilization via improved organ assessment and real-time decision support, improving allograft preservation and optimization prior to implantation, improving allograft longevity following implantation, and expanding pediatric kidney transplantation. 42 Lia et al sought to evaluate the effects of acute kidney injury (AKI) on donation after circulatory death (DCD) kidneys with respect to graft outcomes and overall survival. In a retrospective analysis of 135,644 patients from the United Network for Organ Sharing dataset, relative to donation after brain death (DBD) allografts, DGF was more commonly seen in all DCD allografts (OR 2.49, P < .001).…”
Section: Future Of Organ Allocationmentioning
confidence: 99%
“…KT provides better QoL than dialysis [65,169,170]. Although the average time spent on the TWL varies among countries, it has been estimated that 5% to 15% of the patients remain enlisted long enough to be either removed from the list or die before receiving a suitable organ [52,171,172]. In 2019, among 101000 patients waiting for a KT in the US, more than 8000 died or were suspended due to deteriorating medical conditions, with a median wait-time for a deceased-donor kidney exceeding five years [173].…”
Section: Quality Of Life On the Transplant Waiting Listmentioning
confidence: 99%
“…Current projections suggest that the prevalence of ESRD will further increase in the near future due to the rising incidence of diabetes, hypertension, and obesity as well as the progressive aging of the population [193][194][195][196]. It is demonstrated that KT ensures better patient survival and QoL than dialysis, with reduced costs [171,197,198]. Nevertheless, the vast majority of KT candidates spend a considerable amount of time on dialysis before being transplanted [173].…”
Section: Cost Of Dialysis Before Transplantmentioning
confidence: 99%